2017
DOI: 10.1016/j.ajhg.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Ancestry and Demographic History of African-Descendant Maroon Communities from French Guiana and Suriname

Abstract: The transatlantic slave trade was the largest forced migration in world history. However, the origins of the enslaved Africans and their admixture dynamics remain unclear. To investigate the demographic history of African-descendant Marron populations, we generated genome-wide data (4.3 million markers) from 107 individuals from three African-descendant populations in South America, as well as 124 individuals from six west African populations. Throughout the Americas, thousands of enslaved Africans managed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 65 publications
7
61
0
Order By: Relevance
“…To evaluate the impact of sex-biased admixture dynamics in the American populations, we compared the continental ancestry proportions inferred by ADMIXTURE 30 from autosomal data against those estimated for the X chromosome (see Methods). With respect to European ancestry, a paired Wilcoxon test comparing the distribution of autosomal vs X chromosome revealed that the former is significantly higher in all comparisons, suggesting a higher contribution of European males than females in the gene pool of American populations ( Supplementary Figure 8, Supplementary Table 4), in agreement with previous continentalscale reports based on more limited data 25,31,32 . This observation is further supported by the fact that Native American ancestry estimated from autosomal data is always lower (with the exception of Dominican) than that estimated from the X chromosome.…”
Section: Assessing the Impact Of Sex-biased Admixture Of The Americassupporting
confidence: 90%
“…To evaluate the impact of sex-biased admixture dynamics in the American populations, we compared the continental ancestry proportions inferred by ADMIXTURE 30 from autosomal data against those estimated for the X chromosome (see Methods). With respect to European ancestry, a paired Wilcoxon test comparing the distribution of autosomal vs X chromosome revealed that the former is significantly higher in all comparisons, suggesting a higher contribution of European males than females in the gene pool of American populations ( Supplementary Figure 8, Supplementary Table 4), in agreement with previous continentalscale reports based on more limited data 25,31,32 . This observation is further supported by the fact that Native American ancestry estimated from autosomal data is always lower (with the exception of Dominican) than that estimated from the X chromosome.…”
Section: Assessing the Impact Of Sex-biased Admixture Of The Americassupporting
confidence: 90%
“…The legacy of Western Africa on the African genetic diversity in the Americas has been preeminent [5557], along with an impact of Bantu-influenced populations from Central Western Africa, particularly in Brazil South and the Caribbean [55, 56]. These two African ancestries have also been previously documented in Argentina from studies of autosomal [34] and maternal markers [58, 59].…”
Section: Resultsmentioning
confidence: 96%
“…Sex-biased ancestry contributions were inferred by comparing the RFMix characterized fractions of each continental ancestry component on the X chromosomes versus the autosomes as previously described 22;23 . For each individual genome, and each ancestry component, the normalized difference between the X chromosome ancestry fraction and the autosomal ancestry fraction ( ΔAdmix ) is defined as: where F anc,total , F anc,X , and F anc,auto are the genome-wide, X chromosome, and autosome ancestry fractions, respectively.…”
Section: Methodsmentioning
confidence: 99%